Perbandingan Kinerja Perusahaan Dengan Metode Balanced Scorecard - Maharani Winarta, Putu Winna (Fakultas Ekonomi Universitas Gresik, 2023)
The purpose of this study is to compare the performance of two Honda service companies with the Balanced Scorecard method. The research locations are Aneka Motor Denpasar and Niki Baru Motor Denpasar. The results of the financial perspective analysis of Aneka Motor Denpasar's ROA was 8.74% and Niki Baru Motor Denpasar was 4.14%. NPM of Aneka Motor Denpasar is 9.73% and Niki Baru Motor is 1.97%. The Current Ratio of Aneka Motor Denpasar is 353.73% and Niki Baru Motor Denpasar is 211.08%. TATO Aneka Motor Denpasar by 89.89% and Niki Baru Motor Denpasar by 210.13%. Customer retention of Aneka Motor Denpasar in 2021-2022 is 2.23% and Niki Baru Motor Denpasar is 1.02%. Customer acquisition of Aneka Motor Denpasar in 2021-2022 is 2.30% and Niki Baru Motor Denpasar is 1.73%. Customer satisfaction of Aneka Motor Denpasar is 83.51% and Niki Baru Motor Denpasar is 85.19%. Manufacturing Cycle Efficiency of Aneka Motor Denpasar is 0.950 and Niki Baru Motor Denpasar is 0.925. Aneka Motor Denpasar's employee retention for 2021-2022 is 0.00% and Niki Baru Motor is 12.24%. The productivity of Aneka Motor Denpasar employees in 2021-2022 is 0.00% and Niki Baru Motor Denpasar is 92%. Performance results, financial perspective, profitability and liquidity ratios of Aneka Motor Denpasar are superior to Niki Baru Motor Denpasar, while the activity ratio of Niki Baru Motor Denpasar is superior to Aneka Motor Denpasar. Aneka Motor Denpasar's customer perspective is superior to Niki Baru Motor Denpasar. The perspective of Aneka Motor Denpasar's internal business processes is superior to Niki Baru Motor Denpasar. The learning and growth perspective of Aneka Motor Denpasar is superior to Niki Baru Motor Denpasar